Portable and Handheld Raman Instruments Open a Multitude of Applications - Christoph Jansen (CHIMIA)
Fundamental science can sometimes take a long time until it is useful for practical applications, as was the case for Raman spectroscopy. For a long time, it lacked powerful excitation sources and sensitive detectors. However as technology evolved, the number of exciting applications has boomed. Modern Raman spectroscopy has significant advantages, especially in sample preparation. Handheld Raman devices can be very compact and therefore be easily taken to the sample instead of bringing the sample to the lab. Non-destructive measurements obviously are important in gemmology and mineralogy, even in space. In the field of archaeology, pigments in precious ancient paintings, scrolls or books can be identified. This application is also used to identify fraud and falsification and in studies from a medical school they have reported that Raman spectroscopy can be applied to distinguish cancerous tissue from healthy tissue. Due to the mobility and ruggedness of the handheld hardware, Raman spectroscopy can be used for police, firefighters, and military applications for identification of explosives and illicit drugs or warfare substances. With SERS (Surface Enhanced Raman Spectroscopy), Raman spectroscopy can even be used for trace analysis. The SERS effect enhances the sensitivity of the Raman signal by a factor of up to 107. This enables, for example, measuring pesticide residuals on fruit or vegetable surfaces for food safety. It can also be used to identify traces of drugs, e.g. in urine. However, one of the most common Raman-applications is the identity check or verification of incoming goods (RMID) in the pharma industries, directly in the warehouse. Users appreciate the ease of use and the ruggedness of the Raman hardware.